Rapid thermokarst evolution during the mid-Holocene in Central Yakutia, Russia. (December 2017) - Ulrich, Mathias; Wetterich, Sebastian; Rudaya, Natalia; Frolova, Larisa; Schmidt, Johannes; Siegert, Christine; Fedorov, Alexander N; Zielhofer, Christoph
The reconstruction of Holocene thermokarst landform evolution is important to understand the potential impact of current global climate change on permafrost regions. A multi-proxy approach was applied to analyse the sedimentological and biogeochemical characteristics as well as pollen and lacustrine microfossils of a core profile drilled in a small pingo within a large Central Yakutian thermokarst basin (alas). Age–depth modelling with macrofossil 14 C ages reveals high thermokarst deposit sedimentation rates and a complete thermokarst sequence spanning about 900 years during the mid-Holocene between ~6750 and 5870 cal. yr BP. In total, three stages of thermokarst landscape evolution have been identified. Thermokarst processes were initiated at ⩽6750 to 6500 cal. yr BP. Terrestrial conditions changed quickly to lacustrine conditions, and a thermokarst lake rapidly emerged and grew to an estimated size of 120–600 m diameter and 7.5–15 m depth during only ~150 years between ~6500 and 6350 cal. yr BP. The decline of thermokarst processes and lake decrease may have been affected by local hydrological conditions between ~6350 and 5870 cal. yr BP but ceased completely after 5870 cal. yr BP, likely due to climatic changes. Clear evidence for long-lasting and stable lacustrine conditions was not obtained. The study emphasises that short-term warming led to very active permafrost degradation and rapid but locally variable modification of alas and thermokarst evolution.